Hepatocellular Carcinoma: Targeted Therapy and Multidisciplinary Care - McMasters, Kelly M.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Hepatocellular Carcinoma: Targeted Therapy provides a detailed repository of the latest information regarding HCC epidemiology, diagnosis, imaging, pathology, staging, and treatment options. This volume also provides an up-to-date guide for treatment that explores not only traditional treatments, but newer investigational treatment options including surgical resection, liver transplantation, ablation (radiofrequency, microwave), percutaneous ethanol or acetic acid injection, transarterial chemoembolization (TACE), intra-arterial radiation therapy, and systemic chemotherapy. Heptocellular Carcinoma: Targeted Therapy will be of great value to all health care professionals and trainees worldwide who have an interest in the diagnosis and treatment of HCC, including surgeons, medical oncologists, radiologists, radiation oncologists, and pathologists.
Epidemiology and Pathogenesis of HCC -- HCC in patients without cirrhosis or hepatitis.-Pathology considerations -- Diagnosis of HCC: the role of imaging studies -- Screening Programs in High-Risk Populations -- Treatment Overview: Assembling a multidisciplinary team and selection of appropriate treatment options -- Evidence-based guidelines for treatment of HCC in Japan -- Liver Resection for HCC -- Portal Vein Embolization prior to resection -- Laparoscopic Liver Resection for HCC -- Liver Transplantation for HCC -- Resection and reconstruction of inferior vena cava and hepatic veins for advanced HCC -- Radiofrequency ablation for HCC -- Microwave ablation -- Transarterial Chemoembolization -- Intra-arterial chemotherapy bead therapy -- Radioactive microsphere therapy.-Targeted Therapies for HCC -- Systemic Therapy Options for HCC -- Patient follow-up strategies and salvage therapy for recurrence.
Keywords: Medicine; Interventional radiology; Gastroenterology; Oncology; Cancer -- Surgery; Pathology; Medicine & Public Health; Surgical Oncology; Oncology; Pathology; Interventional Radiology; Gastroenterology